Metilación del ADN en pacientes con diabetes mellitus tipo 2: factores y dianas moleculares. Revisión sistemática - Maza Paredes, José Miguel (2024)
Type 2 diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to insulin resistance and progressive dysfunction of the beta cells of the pancreas. This remains a pandemic with no clear solution in sight. It has been shown that epigenetic mechanisms can mediate the expression of genes involved in pancreatic beta-cell function, as well as the regulation of metabolism and glycemic homeostasis. To this end, this systematic review aimed to outline the determinants that modify DNA methylation patterns and to describe the molecular targets susceptible to variations in DNA methylation in patients with DM2. An exhaustive search was performed using combinations with Mesh terms and the Boolean AND operator in Lilacs, Pubmed and SciELO. With the help of the PRISMA method, 21 studies were selected, whose methodological quality was evaluated with the JBI tool. Two articles were eliminated for having a high risk of bias, leaving a total of 19 articles to meet the objectives. Among the risk factors involved in epigenetic regulation we found age, sex, diet, obesity and the intrauterine environment, which affect DNA methylation patterns and exacerbate the risk of DM2, whereas physical activity emerges as a protective factor since it improves insulin sensitivity, helps to control weight and consequently decreases the risk of developing DM2. It was also found that the molecular targets susceptible to variations in DNA methylation are pancreatic, adipose, skeletal, liver and blood tissues, which can be hypo- or hypermethylated and these modifications are involved in the regulation of insulin sensitivity, energy metabolism, inflammation and mitochondrial function. In conclusion, both protective and risk factors directly influence pancreatic beta-cell function/dysfunction; likewise, silencing and overexpression of different molecular targets may contribute to the development and progression of DM2 by affecting key processes such as insulin secretion, insulin resistance and pancreatic beta-cell dysfunction